\( \leqslant \) Solve the following equation by making an appropriate substitution. \[ 3 x^{-2}-13 x^{-1}+12=0 \] The solution set is \( \} \). Tvpe an integer or a simolified fraction Tyne exact answers using radicals as nee
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
Let’s make the substitution \( y = x^{-1} \). Therefore, the equation \( 3 x^{-2}-13 x^{-1}+12=0 \) transforms into: \[ 3y^2 - 13y + 12 = 0. \] Now we can solve this quadratic equation using the quadratic formula, \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): Here, \( a = 3 \), \( b = -13 \), and \( c = 12 \): \[ y = \frac{13 \pm \sqrt{(-13)^2 - 4 \cdot 3 \cdot 12}}{2 \cdot 3} = \frac{13 \pm \sqrt{169 - 144}}{6} = \frac{13 \pm \sqrt{25}}{6} = \frac{13 \pm 5}{6}. \] This results in two potential values for \( y \): 1. \( y = \frac{18}{6} = 3 \) 2. \( y = \frac{8}{6} = \frac{4}{3} \) Recalling the substitution \( y = x^{-1} \), we can solve for \( x \): 1. \( x = \frac{1}{3} \) 2. \( x = \frac{3}{4} \) Thus, the solution set is: \[ \left\{ \frac{1}{3}, \frac{3}{4} \right\}. \]